The Effect of Photoperiod on the Growth of Stevia rebaudiana in vitro - Ramadhan, Muhammad Syah; Esyanti, Rizkita Rachmi; Iriawati, Iriawati; Rahmawati, Andira (School of Life Sciences and Technology, Institut Teknologi Bandung, 2024)
Stevia rebaudiana, the source of non-caloric natural sweeteners in the form of steviol glycosides, is a plant with a poor germi- nation rate.Therefore, micropropagation is a potential alternative method to propagate the plants in a large number. Light is an important factor for photosynthesis, so changing the intensity, quality, and duration of lighting can affect plant growth. Photo- period, the duration of light within 24hour period, has been known to influence the growth of S. rebaudiana grown in ex vitro conditions. The purpose of this study is to investigate the effect of various photoperiod (8, 12, and 16 hours) on the growth of S. rebaudiana in vitro. The node segments from ex vitro grown S. rebaudiana plants were cultured on solid MS media supple- mented with 1.13mg/L BA and 0.35 mg/L IAA. The shoots were rooted on solid half-strength MS media containing 0.1 mg/L IAA. For acclimatization, therooted shoots were grown on a mixture of fertile soil, burnt rice husk, cocopeat, and manure. The photoperiod treatment was applied from the beginning to the end of the experiment. Our results showed that the highest shoot length was found under 16 hour photoperiod. On the otherhand, root number and root length were not affected by photoperiod. Additionally, a 16 hour photoperiod increased shoot length (5.9 cm) compared to a 12-hour (3.48 cm) and 8-hour photoperiod (3.08 cm) after 5 weeks of acclimatization. A 16 hour photoperiod also producedhighest total leaf fresh weight (0.2 g). Howev- er, different photoperiods did not significantly affect leaf number and leaf area. In conclusion, 16 hour photoperiod is the best condition for S. rebaudiana micropropagation.